2012
DOI: 10.1007/s00330-012-2457-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance 4D flow analysis of cerebrospinal fluid dynamics in Chiari I malformation with and without syringomyelia

Abstract: 4D-PC flow imaging allowed comprehensive analysis of CSF flow in patients with Chiari I malformation. Alterations of CSF hydrodynamics were most pronounced in patients with syringomyelia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
84
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 32 publications
11
84
2
Order By: Relevance
“…Tonsillar motion reflects displaced volume from the cranial cavity during the cardiac cycle and is a balance of 2 parameters: cranial volume and cardiac output (to the cranium). Morphometric and anatomical studies indicate no differences in cranial volume between CM-I patients with and without syringes, as demonstrated by similar degrees of crowding (reflected by the posterior fossa/intracranial volume ratio), 54 cross-sectional CSF area at the foramen magnum, 5 and degree of tonsillar ectopia (as demonstrated in the current study). 5,34 No anecdotal or experimental data suggest that cardiac output differs between CM-I patients with and without syringomyelia.…”
Section: Association Between Cerebellar Tonsillar Motion and Syringomsupporting
confidence: 71%
See 1 more Smart Citation
“…Tonsillar motion reflects displaced volume from the cranial cavity during the cardiac cycle and is a balance of 2 parameters: cranial volume and cardiac output (to the cranium). Morphometric and anatomical studies indicate no differences in cranial volume between CM-I patients with and without syringes, as demonstrated by similar degrees of crowding (reflected by the posterior fossa/intracranial volume ratio), 54 cross-sectional CSF area at the foramen magnum, 5 and degree of tonsillar ectopia (as demonstrated in the current study). 5,34 No anecdotal or experimental data suggest that cardiac output differs between CM-I patients with and without syringomyelia.…”
Section: Association Between Cerebellar Tonsillar Motion and Syringomsupporting
confidence: 71%
“…6,11 The recent improvements in cine MRI technology have also enabled the first comparisons between CM-I patients with and without syringomyelia. Cousins and Haughton 11 reported cerebellar tonsillar motion to be 22% greater in CM-I patients with syrinx than in those without syrinx (no p values were calculated), whereas Bunck et al 5 found no significant differences between groups. The small sample sizes of both studies (11 CM-I and 20 CM-I patients, respectively) limited the study power, and both assumed that tonsillar motion only occurs in the superoinferior direction.…”
mentioning
confidence: 95%
“…At present, MRI techniques are being developed to measure CSF pressure gradients noninvasively [14], but these methods are not in standard use and have not been validated. In principle, changes in CSF pressure gradients are related to alterations in impedance to CSF motion, CSF velocities [15][16][17][18][19][20][21][22], neural tissue motion [23][24][25], and craniospinal compliance [26][27][28]. We suspect that alterations in each of these biomechanical parameters could prove useful to quantify the biomechanical environment near the CVJ in CMI.…”
Section: Introductionmentioning
confidence: 99%
“…Inertial properties of fluid may in some geometries create a pattern of flow called "flow separation," which results in eddy currents and vortices (Fig 4). 6 Flow not aligned with the spinal axis can be demonstrated by computational fluid dynamics (Fig 5) 7 and by PCMR when multiple gradient directions are used. 6 The anatomy of the subarachnoid space increases the complexity of CSF flow patterns in the spine.…”
mentioning
confidence: 98%
“…6 Flow not aligned with the spinal axis can be demonstrated by computational fluid dynamics (Fig 5) 7 and by PCMR when multiple gradient directions are used. 6 The anatomy of the subarachnoid space increases the complexity of CSF flow patterns in the spine. The flow velocities in any axial section of the spine have nonuniform distributions throughout the cardiac cycle, as PCMR and flow simulations show (Figs 6 and 7).…”
mentioning
confidence: 98%